KONFLIK ANAK PAMUTIA BRONDOL SAWIT DENGAN PEMILIK LAHAN PERKEBUNAN KELAPA SAWIT JORONG KAMPUNG KAJAI, KABUPATEN PASAMAN - Pelna Marsela; Inoki Ulma Tiara; Yuhelna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the conflict between child workers involved in pamutia brondol sawit (loose oil palm fruit collectors) and oil palm plantation landowners in Jorong Kampung Kajai, Pasaman Regency. The conflict arises within a community whose economy largely depends on the plantation sector, where the activity of collecting loose palm fruits—initially permitted—has developed into violations such as harvesting fresh fruit bunches directly from trees, hiding harvested bunches, and taking loose fruits already collected by landowners. This research aims to identify the factors causing the conflict and to analyze the forms of conflict resolution carried out by the local community. The study employs a descriptive qualitative approach with purposive sampling techniques. Data were collected through observation, interviews, and document analysis, and analyzed using the interactive model of Miles and Huberman. The theoretical framework is based on Randall Collins’ conflict theory, which emphasizes competition over material resources as a trigger of social conflict. The findings reveal that the conflict is driven by economic pressures, the increasing number of children involved as collectors, and weak social control. The forms of conflict include both open and latent conflicts, some of which have led to acts of violence. Conflict resolution is conducted through customary deliberation and the imposition of fines as a local wisdom–based mechanism. These findings highlight the importance of strengthening the roles of families, customary institutions, and village authorities in preventing economically driven social conflicts at the local level. Keywords: Social Conflict, Child Labor, Oil Palm Loose Fruit Collectors, Conflict Resolution.